1986
DOI: 10.1111/j.1151-2916.1986.tb04821.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Fracture Behavior of Monolithic Fuel Cell Tapes

Abstract: This paper summarizes the stress and fracture analyses of a three-layer ceramic composite which is a fundamental building block for the monolithic solid oxide fuel cell currently being developed at Argonne National Laboratory. A small difference in the coefficients of thermal expansion of different layers can result in large stresses and cause cracking parallel to the plane of the layers. A simple fracture model for a three-layer composite has been developed. The cracking behavior predicted by the model is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 4 publications
2
23
0
1
Order By: Relevance
“…Majumdar et al reported a detailed study about the stress and fracture behaviour of a three-layer ceramic SOFC developed at the Argonne National Lab [17]. They concluded that small differences in the TECs of different layers results in layer stresses and causes cracking parallel to the plane of the layers.…”
Section: Thermo-mechanical Mismatchmentioning
confidence: 99%
“…Majumdar et al reported a detailed study about the stress and fracture behaviour of a three-layer ceramic SOFC developed at the Argonne National Lab [17]. They concluded that small differences in the TECs of different layers results in layer stresses and causes cracking parallel to the plane of the layers.…”
Section: Thermo-mechanical Mismatchmentioning
confidence: 99%
“…With the above understanding, the failure at the SABS-0/ZrO 2 interface can be analysed as follows. The fracture strength of the ZrO 2 electrolyte is ≥ 200 MPa, which is much greater than the tri-layer assembly rupture strength (15 MPa) [34][35][36]. Even with the consideration of the thin electrolyte layer, it is unlikely that the ZrO 2 electrolyte is the failure initiation point.…”
Section: Rupture Strengthmentioning
confidence: 96%
“…To avoid cell cracking and delamination during cell fabrication and operation, the CTE of anode-support is required to match with those of other cell components [25]. Without adding LaNbO 4 , the CTE of the NiO-YSZ composite was 13.6 Â 10 À6 K À1 , which is in agreement with that reported in literature [26]; adding 30 wt.% of LaNbO 4 into the NiO-YSZ, the CTE of 30LNO decreased to 12.4 Â 10 À6 K À1 , which is even closer to that of YSZ electrolyte (10.3 Â 10 À6 K À1 [26]).…”
Section: Effect Of Lanbo 4 Addition On Thermal Expansion Behaviormentioning
confidence: 99%